Utilization of organic chromium from tannery waste on reducing transportation stress and shortening recovery period at beef cattle - Santosa, U; Tanuwiria, U.H; Yulianti, A; Suryadi, U (Indonesian Journal of Animal and Veterinary Sciences, 2012)
Transportation increases stress that subtantially decreases body weight and feed comsumption even weight gain loss after arriving at the location of fattening. A research has been conducted to study the effects of organic chromium from tannery wastes on the level of transportation stress and recovery period in beef cattle fattening. Twenty Ongole crossbreed cattles were transported from the Wirasaba Feedlot at Purbalingga in Central Java to the Agro Citra Buana Semesta Feedlot in Malangbong-Garut in West Java for about 18 hours. Completely Randomized Design (CRD) was applied, wih four repetitions. The              Cr-organic was given seven days before and after transportation. Dose of Cr-organic used was: R0 = control diet without         Cr-organic, R1 = R0 + 1.5 ppm, R2 = R0 + 3.0 ppm, R3 = R0 + 4.5 ppm, R4 = R0 + 6.0 ppm. Results showed that 3.0 ppm organic chromium of the dry matter of ration tended to affect physiology and haematological conditions, as well as decreased weight loss, shortened recovery time, improved weight gain. It is concluded that organic chromium supplementation was able to lowered stress levels, shortened recovery time, and increased daily gain for one week recovery process, especially at dose of 3.0 ppm. Key Words: Organic Chromium, Leather Tanning, Transportation Stress, Recovery Period, Weight Loss